2014
DOI: 10.4161/cbt.29922
|View full text |Cite
|
Sign up to set email alerts
|

Production of IL-1β by bone marrow-derived macrophages in response to chemotherapeutic drugs

Abstract: Cytotoxic chemotherapeutic drugs, especially when used in combination, are widely employed to treat a variety of cancers in patients but often lead to serious symptoms that negatively affect physical functioning and quality of life. There is compelling evidence that implicates cytotoxic chemotherapy-induced inflammation in the etiology of these symptoms. Because IL-1β plays a central role as an initiator cytokine in immune responses, we compared doxorubicin, a drug known to induce IL-1β production, with ten ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“… 37 It suggested that activation of the NLRP3-dependent inflammasome might be derived from the macrophages. 35 , 38 …”
Section: Discussionmentioning
confidence: 99%
“… 37 It suggested that activation of the NLRP3-dependent inflammasome might be derived from the macrophages. 35 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that treatment of mice with doxorubicin induced IL-1β release from bone marrowderived macrophages via activation of the NLRP3 inflammasome [36,37]. Recently, Kobayashi et al suggested that NLRP3 plays a role in doxorubicin-induced cardiotoxicity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Common inflammatory mediators, including TGFβ, TNFα, PGE2, HGF, and IL1β, drive chronic obstructive pulmonary disease, such as pulmonary fibrosis, and emphysema. These mediators also play essential roles in the regulation of bone marrow homeostasis, affecting immune cell survival, migration, proliferation, and differentiation [125130]. Thus, it is possible that these molecules, altered in these pulmonary disorders, participate in bone marrow alterations that will affect lung cancer development.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%